The well‐posedness of the double‐diffusive convection system in a bounded domain. (26th April 2018) - Chen, Fei; Guo, Boling; Zeng, Lan
Abstract : In this paper, we consider the well‐posedness of the initial and boundary value problem for the double‐diffusive convection system in a bounded domain Ω ⊂ R 3 . We first prove the local existence of the unique strong solution with large initial data in H 0 1 ( Ω ) and then extend it to a global one provided the L 2 norm of the initial data is small.